Estimating Short Run and Long Run Coefficients of Fundamentals Factors with Growth and Momentum Factor: Evidence from Emerging Markets - Adnan Shoaib; Muhammad Ayub Siddiqui (Australasian Accounting, Business and Finance Journal, 2017)
This study examines the long term relationship of risk premium and fundamental factors in emerging stock markets of China, India and Pakistan keeping in view leading contribution of Fama and French (1992) and Carhart (1997) models. Contrary to the macroeconomic multifactor models, this study incorporates firm-specific risk factors related to the market premium; size (SMB), value (HML), momentum (WML) and growth (UMD) as determinants of risk premium. The firm-specific growth factor is incorporated based on evidence from Ho, Strange, and Piesse (2008) by employing (UMD) which is based on assets to market equity of the firm. Sample of 1198 companies from the three emerging markets for the period of 2001-2013 depicts market risk premium as the leading factor affecting risk premium in Indian and the Pakistani markets. Results reveal market momentum being high enough to overestimate coefficients in the short run. However, the relationship is stabilized and adjusted in the long run. Chinese markets, where all the risk factors seem to play their role to determine risk premium, are relatively much stable and grown-up and clearly represent maturity of the Chinese markets. Distinction between the short run and long run might be useful for the investors of the three emerging economies. According to the principle of high risk associated with high returns, small value happens to deliver higher returns with higher volatility. The growth stocks outperform value stocks in these economies.
Keywords: Fama-French; HML; SMB; WML; Market Gearing; Global Financial Crises; Long term relationship; Partial Adjustment Model